The Israeli species of the subtribe Xylenina (Lepidoptera: Noctuidae, Xyleninae) - V. D. Kravchenko (SHILAP Revista de lepidopterología, 2008)
Twenty-one species in eight genera of the subtribe Xylenina are currently known in Israel. Four of them are new records for fauna of Israel: T. cypreago, A. rupicarpa, L. ledereri and X. vetusta. Most of the known species belong to the genera Agrochola (10), Lithophane (3), Conistra (2) and Xylena (2). Another four genera (Tiliacea, Xanthia, Maraschia, Jodia) contain one species each. Most of the species are Mediterranean (10), or European and Palearctic elements (6) while four species are endemics of the Levant: (A. pauli, A. hypotaenia, A. staudingeri, C. acutula). One species (A. scabra) is an Iranian element. About half of the species (10) occur mostly in the forests of Mt. Hermon and adjacent areas of northern Israel. Only the larvae of two species (A. helvola and J. croceago) were collected in the 1960's and have not been recorded since. All the species are univoltine autumn and winter species that fly from October to February with the highest rate of occurrence from December to January.